Health-related quality of life of carfilzomib- and daratumumab-based therapies in patients with relapsed/refractory multiple myeloma, based on German benefit assessment data - Weisel, Katja; Ludwig, Heinz; Rieth, Achim; Lebioda, Andrea; Goldschmidt, Hartmut (Quality of life research, 2020)
Carfilzomib and daratumumab are licensed in relapsed/refractory multiple myeloma (RRMM), but no head-to-head trials have been conducted.
Published online: 24 September 2019
Gesehen am 14.04.2020